PROFILING THE TURKISH UNDERGRADUATE STUDENTS WHO LEARN JAPANESE: THROUGH THE ATTITUDES TOWARDS JAPANESE SOCIETY AND LANGUAGE - Tolga ÖZŞEN (Fırat University, 2019)
In recent years, due to the extend of economic relationship between Turkey and Asia (particularly Japan), interest on Asian (particularly Japanese) language have also been increasing as well. Japanese Language education is one of the most organized and widespread Asian language in Turkey. As we are in information age, “far” cultures and languages such as Japanese are getting closer due to integration of communication techonology to the daily life. At this point, to stabilize and make the structure of organizations stronger in Japanese language education, education programs and methodologies are needed to be developed, and covered students needs that change and vary. Discussing the general profile of Japanese Language students can be considered in two terms: short-mid term and long term. In the case of short-mid term, this profile discussion can lead us in terms of reconsideration of the education programs and methodologies used in Japanese Language education. On the other hand, in the long term, this profile discussion can contribute to the development process of national strategies on Japanese Language education. Therefore, in order to create Japanese learner profiles reflecting socioeconomis condiditions of Turkey is the main aim of this paper. ‘Who (what kind of people) learns Japanese’ will be the main question that shapes the content of this study. In this paper, firstly, general socioeconomic conditions of the students will be discussed. Secondly, attitudes of the students concerning Japanese language, culture and society will be analyzed in different aspects and attempted to establish general Japanese student profiles.